MEMBANGUN KEBERHASILAN: PENGARUH KETERLIBATAN ORANG TUA PADA PRESTASI AKADEMIK - Alin Nisa Andryani; Miranti Rasyid; Aulia Suhesty; Aulia Ramdani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to examine the effect of parental involvement on students’ academic achievement. Academic achievement is an indicator of learning success influenced by various internal and external factors, one of which is parental involvement in supporting students’ learning processes. Although parental involvement has been widely examined among students in general, studies that specifically investigate parental involvement among high-achieving senior high school students remain relatively limited. High-achieving students are important to examine because they have distinct academic characteristics, such as learning independence, high achievement demands, and the need for support that is appropriate to their stage of adolescent development. This study employed a quantitative approach. The subjects were students from a school with high academic achievement in East Kalimantan, with a total sample of 213 students selected using simple random sampling. Data were collected using a Likert scale to measure perceived parental involvement, which included involvement at home, involvement at school, and communication-based involvement. The data were analyzed using simple linear regression. The results showed that parental involvement did not have a significant effect on students’ academic achievement; therefore, the hypothesis of this study was not supported. These findings suggest that among high-achieving senior high school students, parental involvement is not the main predictor of academic achievement, and other factors are presumed to play a more dominant role in influencing students’ academic outcomes. The implication of this study indicates that parental involvement among adolescents needs to be directed more toward emotional support, trust, and the strengthening of learning autonomy, rather than merely direct academic supervision. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh keterlibatan orang tua terhadap prestasi akademik siswa. Prestasi akademik merupakan indikator keberhasilan belajar yang dipengaruhi oleh berbagai faktor internal dan eksternal, salah satunya keterlibatan orang tua dalam mendukung proses belajar siswa. Meskipun keterlibatan orang tua telah banyak diteliti pada siswa secara umum, studi yang secara khusus mengkaji keterlibatan orang tua pada siswa SMA berprestasi tinggi masih relatif terbatas. Padahal, siswa berprestasi tinggi penting diteliti karena memiliki karakteristik akademik yang berbeda, seperti kemandirian belajar, tuntutan pencapaian yang tinggi, serta kebutuhan dukungan yang sesuai dengan tahap perkembangan remaja. Penelitian ini menggunakan pendekatan kuantitatif. Subjek penelitian adalah siswa dari sekolah dengan prestasi akademik tinggi di Kalimantan Timur dengan jumlah sampel sebanyak 213 siswa yang dipilih menggunakan teknik simple random sampling. Data dikumpulkan menggunakan skala Likert untuk mengukur persepsi keterlibatan orang tua yang mencakup keterlibatan di rumah, di sekolah, dan berbasis komunikasi. Analisis data dilakukan menggunakan regresi linier sederhana. Hasil penelitian menunjukkan bahwa keterlibatan orang tua tidak berpengaruh signifikan terhadap prestasi akademik siswa, sehingga hipotesis dalam penelitian ini tidak diterima. Temuan ini menunjukkan bahwa pada siswa SMA berprestasi tinggi, keterlibatan orang tua bukan merupakan prediktor utama prestasi akademik, sehingga terdapat faktor lain yang diduga lebih dominan dalam memengaruhi capaian akademik siswa. Implikasi dari penelitian ini menunjukkan bahwa keterlibatan orang tua pada remaja perlu lebih diarahkan pada dukungan emosional, pemberian kepercayaan, dan penguatan otonomi belajar, bukan hanya pada pengawasan akademik secara langsung.